Training health workers for magnesium sulfate use reduces case fatality from eclampsia: results from a multicenter trial. (13th April 2013) - Okonofua, Friday E.; Ogu, Rosemary N.; Fabamwo, Adetokunbo O.; Ujah, Innocent O.; Chama, Calvin M.; Archibong, Eric I.; Onah, Hyacinth E.; Galadanci, Hadiza S.; Akuse, James T.
Abstract Objective To investigate the effectiveness of an intervention aimed at improving the case management of eclampsia. Design A multi‐center intervention study. Setting Six teaching hospitals in Nigeria. Sample Clinical records of cases of eclampsia treated before and 1 year after the intervention. Methods Doctors and midwives in selected hospitals were re‐trained to manage eclampsia using magnesium sulfate according to the Pritchard protocol. Main outcome measures Eclampsia case fatality rates, maternal and perinatal mortality rates before and after the intervention. Results A total of 219 cases of eclampsia were managed over a 12‐month period. There were seven maternal deaths. The post intervention case fatality rate of 3.2% was significantly less than the pre‐intervention rate of 15.1% (p < 0.001). The overall maternal and perinatal mortality ratios and rates respectively in the hospitals declined from 1199.2 to 954 per 100 000 deliveries and 141.5 to 129.8 per 1000 births, respectively (p > 0.05). Conclusion An intervention to build the capacity of care‐providers to use an evidence‐based protocol for the treatment of eclampsia in Nigeria was successful in reducing associated case fatality rate. The increased and widespread use of such an intervention in maternity units might contribute to the reduction of maternal mortality in low‐income countries.